Wear studies on ZrO2-filled PEEK as coating bearing materials for artificial cervical discs of Ti6Al4V - Song J.; Liu Y.; Liao Z.; Wang S.; Tyagi R.; Liu W. (My University, 2025)
Polyetheretherketone (PEEK) and its composite coatings are believed to be the potential candidates' bio-implant materials. However, these coatings have not yet been used on the surface of titanium-based orthopedics and joint products and very few investigations on the tribological characteristics could be found in the published literature till date. In this study, the wettabilities, composition and micro-hardness were characterized using contact angle measurement, scanning electron microscopy (SEM) and hardness tester. The tribological tests were conducted using a ball-on-disc contact pair under 25% newborn calf serum (NCS) lubricated condition. For comparison, bare Ti6Al4V was studied. The obtained results revealed that those PEEK/ZrO2 composite coatings could improve the tribological properties of Ti6Al4V significantly. Adhesive wear and mild abrasive wear might be the dominant wear and failure mechanisms for PEEK/ZrO2 composite coatings in NCS lubricated condition. After comprehensive evaluation in the present study, 5 wt.% ZrO2 nanoparticles filled PEEK coating displayed the optimum tribological characteristics and could be taken as a potential candidate for the bearing material of artificial cervical disc. © 2016 Elsevier B.V.